Pengaruh Blanching terhadap Sifat Antioksidasi Sirup Kunir Putih (Curcuma mangga Val.) - Dwiyati Pujimulyani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
The research on the effect of blancing on antioxidant properties of white saffron syrup (Curcuma mangga Val) was conducted. The general purpose of this research is to have a white saffron syrup with a high antioxidant activity. The specific objectives were to know the effect of temperature and blanching time on the linoleic acid oxidation. White saffron tubers of mangga sp. were washed, peeled, and blanched at (i) 80oC, (ii) 100oC for (i) 5 and (ii) 10 minutes in the media of (i) 0.05% citric acid solution (ii) 0.8% ascorbic acid solution and (iii) distilled water. Blanched white saffron then was grated, manually pressed with filter cloth to get white saffron juice. The juice was added with sugar (ratio 100:130) and other ingredients i.e: 0.1% CMC, 0.128% citric acid, 0.031% benzoic acid, then boiled for 20 minutes to get the syrup. The antioxidant activity of the syrup was tested according to FTC and TBA methods. The results showed that the antioxidant activity of white saffron syrup blanched at 80oC for 5 minutes was higher than its activity at 100oC and for 10 minutes, respectively. Blanching in citric acid medium at 80oC for 5 minutes resulted a highest antioxidant activity of the white saffron syrup